A Modeling Study of the Micro-finance İmpact on the Economic Performance of Micro-enterprises and the Well-being of Borrowers in Morocco: Case of Tangier-Tetouan - Al Hoceima Region - Amrani, Mohamed B. S.; Hamza, Faris; Mostapha, El Hachloufi (International Journal of Economics and Financial Issues, 2018)
This paper aims to study the impact of microfinance on the performance of micro-enterprises and the well-being of borrowers. From a methodological point of view, we have opted for an econometric study based on a multiple linear regression model realized on a sample of 200 Microcredit beneficiaries from two reference institutions in the Tangier-Tetouan-Al-Hoceima region. The results of this research indicate that micro-credits positively and partially influence the economic performance of micro-enterprises and the well-being of beneficiaries. The linear regression model shows that the economic performance of micro-enterprises is explained by two variables, namely: profit and savings while social performance (well-being of beneficiaries) is explained by two endogenous variables namely: improving the level of schooling of children, as well as improving food. Keywords: Microcredit, Impact, Economic Performance, Social Performance. JEL Classifications: G2, O1